Posterior cortical atrophy: A rare variant of Alzheimer's disease - Michael A. Meyer; Stephen A. Hudock (MDPI AG, 2018)
Posterior cortical atrophy is a rare condition first described in 1988 involving progressive degeneration and atrophy of the occipital cortex, often recognized after an unexplained homonymous hemianopsia may be discovered. We report a case in association with Alzheimer's disease in a 77-year-old female, who underwent brain single-photon emission computed tomography as well brain positron emission tomography using Florbetapir to further evaluate progressive cognitive decline. The patient had also been followed in Ophthalmology for glaucoma, where a progressive unexplained change in her visual field maps were noted over one year consistent with a progressive right homonymous hemianopsia. This rare combination of findings in association with her dementia led to a detailed review of all her imaging studies, concluding with the surprising recognition for a clear hemi-atrophy of the primary left occipital cortex was occurring, consistent with Alzheimer's disease affecting the primary visual cortex. Further awareness of this disease pattern is needed, as Alzheimer's disease typically does not affect the primary visual cortex; other conditions to consider in general include Lewy Body dementia, cortico-basal degeneration and prion disease.